Du travailleur au malade : retour sur la reconstitution du parcours professionnel de patients atteints de cancer en Seine-Saint-Denis - Flaviene Lanna (La Nouvelle Revue du Travail)
Since 2002, Giscop93 (working out of Seine Saint Denis, a northern suburb of Paris) has conducted an ongoing survey into occupational exposure to carcinogens and whether these cancers qualify for workers’ compensation. The first stage consists of a subtle reconstruction of a patient’s job history based on a qualitative interview analyzed subsequently by industrial health experts looking to identify possible exposures. The article also looks at the method used to reconstruct individual job histories and tries to show some of the social dimensions that play a role in constructing a patient’s narrative.